2017
DOI: 10.20396/bjos.v16i0.8650494
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in technological armamentarium and treatment among Brazilian endodontists

Abstract: Aim:To determine the current trends in technological armamentarium and endodontic treatment among Brazilian endodontists. Methods: A total of 279 endodontists answered a web-based survey questionnaire about their region of activity in Brazil and years as a specialist, average number of endodontic cases treated per month, number of visits to complete the treatment, use of rubber dam for isolation, type of irrigant, obturation technique and device used for this purpose, temporary filling materials, and greater d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 20 publications
(49 reference statements)
2
13
1
Order By: Relevance
“…With a greater number of cases performed per week, saving time by using NiTi-RIs is paramount, as they significantly reduce instrumentation times [ 21 ]. A very recent study found that dentists performed significantly greater number of RCTs when using NiTi-RIs compared to manual preparation [ 32 ]. The highest proportion of respondents (45.3%), in the current study, used NiTi-RIs because of faster root-canal preparation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a greater number of cases performed per week, saving time by using NiTi-RIs is paramount, as they significantly reduce instrumentation times [ 21 ]. A very recent study found that dentists performed significantly greater number of RCTs when using NiTi-RIs compared to manual preparation [ 32 ]. The highest proportion of respondents (45.3%), in the current study, used NiTi-RIs because of faster root-canal preparation .…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of dentists (85%), in the current study, did not use NiTi-RIs because of high cost. Also, most dentists in Wales (62%) reported high cost for not using RIs [ 32 ]. Such a factor may reflect the real willingness of these dentists to use NiTi-RIs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other studies that reported the prevalence of use of magnification devices are shown in Table 2 . [ 7 13 14 15 16 17 18 19 ]…”
Section: Prevalence Of Magnification Devices Usagementioning
confidence: 99%
“…A study determined the latest trends in technological armamentarium in endodontic treatment among Brazilian endodontists revealed that 67.38% of endodontists utilized magnification tools in which 23.66% of them use magnifying loupes in their practices. 9 Wong et al have compared the time needed for performing non-surgical endodontic therapy with or without a magnifying loupe. Ninety-six patients, who required non-surgical root canal treatment, were treated by two dentists from the University of Hong Kong and two dentists from Peking University.…”
Section: Discussionmentioning
confidence: 99%